A new species of Ochterus Latreille (Hemiptera Ochteridae) from the Philippines - Gapud, V.P (Asia life sciences :the international journal of life sciences., 1995)
"Ochiterus surigaoensis Gapud, a new species from Surigao del Sur, is described and its salient features illustrated."